2015
DOI: 10.1111/mec.13113
|View full text |Cite
|
Sign up to set email alerts
|

Variation in promiscuity and sexual selection drives avian rate of Faster‐Z evolution

Abstract: Higher rates of coding sequence evolution have been observed on the Z chromosome relative to the autosomes across a wide range of species. However, despite a considerable body of theory, we lack empirical evidence explaining variation in the strength of the Faster‐Z Effect. To assess the magnitude and drivers of Faster‐Z Evolution, we assembled six de novo transcriptomes, spanning 90 million years of avian evolution. Our analysis combines expression, sequence and polymorphism data with measures of sperm compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 105 publications
(309 reference statements)
8
122
1
Order By: Relevance
“…Chromosomal location was defined by orthology in chicken, allowing us to capitalize on the stability of avian genomes (18). Due to the incomplete Z chromosome dosage compensation in birds (21)(22)(23) and the unique evolutionary forces shaping sex chromosomes (24)(25)(26)(27), we focus only on the autosomal orthologs here and have dealt with the Z-linked orthologs separately (28).…”
Section: Resultsmentioning
confidence: 99%
“…Chromosomal location was defined by orthology in chicken, allowing us to capitalize on the stability of avian genomes (18). Due to the incomplete Z chromosome dosage compensation in birds (21)(22)(23) and the unique evolutionary forces shaping sex chromosomes (24)(25)(26)(27), we focus only on the autosomal orthologs here and have dealt with the Z-linked orthologs separately (28).…”
Section: Resultsmentioning
confidence: 99%
“…The distinct pattern of inheritance in sex chromosomes means that they experience evolutionary forces different from the rest of the genome (Mank et al 2010), and they have hence been subject to a number of evolutionary studies in birds (Wang et al 2014;Zhou et al 2014), also using transcriptomic data (Balakrishnan et al 2013;Künstner et al 2010;Ramstad et al 2016;Wright et al 2015). Wright et al (2015) studied sequence and expression data of sex chromosomes simultaneously in six species of birds using RNA-seq data. The authors found that gene divergence between the species was higher on the Z-chromosome than on autosomal chromosomes.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Chung et al 2015;Mueller et al 2015). Wright et al (2014) [3] {18, 22, 23}; Harrison et al (2015) [3] {18, 22, 23}; Li et al (2015) [2] {3, 22, 24}; Smith et al (2015) [2] {12, 16}; Wright et al (2015) [3] {18, 22, 23} Anser cygnoides Swan Goose a Harrison et al (2015) [3] {18, 22, 23}; Lu et al (2015) [1, 2] {15}; Tariq et al (2015) [2] {28}; Wright et al (2015) [3] {18, 22, 23}; Chen et al (2017b) [2] {28}; Cao et al (2017) Harrison et al (2015) [3] {18, 22, 23}; Wright et al (2014) [3] {18, 22, 23}; Wright et al (2015) [3] {18, 22, 23} Numida meleagris Helmeted Guineafowl Harrison et al (2015) [3] {18, 22, 23}; Wright et al (2015) [3] {18, 22, 23} Pavo cristatus Indian Peafowl Harrison et al (2015) [3] {18, 22, 23}; Wright et al (2015) [3] {18, 22, 23}…”
Section: Characterisation Of Transcriptomesmentioning
confidence: 99%
See 2 more Smart Citations